Study of Tofu Processing in Karya Mulia Tofu Industry in Labusa Village, Konda District, South Konawe Regency - Elsa Saleh; La Ode Alwi; Dhian Herdhiansyah (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
The objective of this research is to know the process of tofu processing in Karya Mulia's tofu industry in Lambusa Village, Konda District, Konawe Selatan Regency. This research was conducted purposively with the background to find out the process of tofu processing in the Karya Mulia tofu industry in Lambusa Village, Konda District, Konawe Selatan Regency. The data sources used are primary data and secondary data. The tofu processing process in Karya Mulia's tofu industry in Lambusa Village, Konda District, South Konawe Regency, with the materials used in the production process, namely water, vinegar, and soybean seeds as the main raw materials with the processing stages of soaking, washing soybeans, cooking, filtering, deposition. , the addition of vinegar, molding, pressing, and cutting tofu.